The Controllable Delivery of Hydrophilic and Hydrophobic Drugs Using Starch Nanoparticle-based Clusters - Montague, E. Coulter (My University, 2020)
Despite the number of treatment methods currently available, cancer remains one of the leading causes of death in Canada and worldwide. It is therefore critical that new and more effective means of combating this disease be developed. Nanoparticles have been extensively investigated for their use in cancer diagnostics, imaging, and most critically in chemotherapeutic drug delivery. One such example is starch nanoparticles (SNPs), which can penetrate dense tumour cores based on their small size and have the capacity to be functionalized and loaded with different types of chemotherapeutic drugs. The size of SNPs, however, limits their potential to reach tumours due to their rapid clearance from the body. To address this challenge, we have fabricated electrostatic complexes – or nanoclusters – composed of cationic SNPs and anionic charge-switchable polymers that remain stable at physiological pH (7.4) and disassemble to release the highly penetrable SNPs when exposed to the acidic (6.5) microenvironment associated with tumours. Furthermore, recent research has indicated that the administration of certain combinations of chemotherapeutic agents can increase the efficacy of targeted cancer therapy while reducing the necessary dose to achieve remission. One example of this is the administration of the relatively hydrophobic EGFR inhibitor erlotinib (Erl), which can synergize cancer cell apoptosis with the more hydrophilic DNA damaging agent doxorubicin (Dox). Here, we reveal the ability to engineer two functionalized SNP variants capable of loading either Dox or Erl that can subsequently be used in nanocluster formation to deliver synergistic antitumour therapy in vitro and in vivo. Though drug loading and dual SNP carrying nanocluster formation remain to be assessed, SNP variant synthesis is an important step towards generating multi-drug delivering nanoclusters.
Keywords: Starch nanoparticle clusters; Cancer therapy; Tumour penetration; Multi-drug therapy